Encounters with violence in Latin America : urban poor perceptions from Colombia and Guatemala - Moser, Caroline O. N. (Routledge, 2004)
Considers the various types of political, social and economic violence that afflict communities and measures the costs and consequences of violence giving a voice to those whose daily lives are dominated by widespread aggression.